2017
DOI: 10.1128/aem.00210-17
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Core Citrus Leaf- and Root-Associated Microbiota: Factors Associated with Community Structure and Implications for Managing Huanglongbing (Citrus Greening) Disease

Abstract: Stable associations between plants and microbes are critical to promoting host health and productivity. The objective of this work was to test the hypothesis that restructuring of the core microbiota may be associated with the progression of huanglongbing (HLB), the devastating citrus disease caused by Liberibacter asiaticus, Liberibacter americanus, and Liberibacter africanus. The microbial communities of leaves (n ϭ 94) and roots (n ϭ 79) from citrus trees that varied by HLB symptom severity, cultivar, locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 61 publications
7
68
0
Order By: Relevance
“…This study is the first to show that endophyte communities in ‘Royal Gala’ were more diverse than those in ‘Braeburn’, suggesting that they were under tighter regulation in ‘Braeburn’. This supported several studies in other plant species such as cotton ( Gossypium hirsutum ) by culture‐dependent method (Adams and Kloepper ), rice ( Oryza sativa ) by PCR‐DGGE (Hardoim et al ) and citrus ( Citrus sinensis ) by Illumina sequencing (Blaustein et al ) that showed host is a major driver of endophyte recruitment. Although this is a new result for cultivars of apple, research into the structure and function of microbial members of the holobiont and the genetic determinants of host recruitment being relaxed or stringent remain unknown.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study is the first to show that endophyte communities in ‘Royal Gala’ were more diverse than those in ‘Braeburn’, suggesting that they were under tighter regulation in ‘Braeburn’. This supported several studies in other plant species such as cotton ( Gossypium hirsutum ) by culture‐dependent method (Adams and Kloepper ), rice ( Oryza sativa ) by PCR‐DGGE (Hardoim et al ) and citrus ( Citrus sinensis ) by Illumina sequencing (Blaustein et al ) that showed host is a major driver of endophyte recruitment. Although this is a new result for cultivars of apple, research into the structure and function of microbial members of the holobiont and the genetic determinants of host recruitment being relaxed or stringent remain unknown.…”
Section: Discussionsupporting
confidence: 83%
“…The relative abundance of endophyte taxa was not determined in this study. Illumina‐based next‐generation sequencing approaches (NGS; metabarcoding) are being used to describe relative abundance of microbial operational taxonomic units (OTUs) in plants and soil (Sun et al ; Zarraonaindia et al ; Blaustein et al ; Wang et al ). Extension of the work to incorporate deep sequencing approaches (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that the microbial communities from different tissues varied significantly and the microenvironments of tree tissues could affect the composition of its microbial community.www.nature.com/scientificreports www.nature.com/scientificreports/ trees 23 . Most previous investigation on citrus-associated microbiomes are analyses on huanglongbing-infected, or specially-treated samples [24][25][26][27][28][29] .Citrus reticulata cv. Chachiensis is an important citrus variety widely cultivated around the world and the orange peel of the fruit was regarded as the valuable material which could be processed as food, tea drinks, and seasoning 30 .…”
mentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ trees 23 . Most previous investigation on citrus-associated microbiomes are analyses on huanglongbing-infected, or specially-treated samples [24][25][26][27][28][29] .…”
mentioning
confidence: 99%
“…Healthy trees had more endophytes compared to symptomatic and asymptomatic trees, which may have been because the www.nature.com/scientificreports www.nature.com/scientificreports/ healthy trees were free of CLas. Previous studies reported that microbial communities in citrus trees are negatively affected by CLas 37,41,42 . In addition, microbial colonization of the branches, stems, roots, and leaves are affected by various factors.…”
Section: Discussionmentioning
confidence: 99%